Development and Validation of Tranexamic Acid Determination in Human Plasma by HPLC-MS/MS method - A. V. Aleshina; T. N. Komarov; O. A. Archakova; D. S. Shchelgacheva; N. S. Bagaeva; V. V. Davydanova; A. Yu. Savchenko; I. E. Shohin (Разработка и регистрация лекарственных средств, 2021)
Introduction. Tranexamic acid is one of the most common drugs used to stop bleeding after trauma, in surgery and gynecology. The most common analytical method for the determination of this compound is reversed-phase high-performance liquid chromatography (HPLC). However, this compound belongs to the group of so-called poorly retained compounds due to its chemical structure. It is necessary to develop an analytical method that will allow the determination of tranexamic acid in human blood plasma with the least time, resource costs and without the use of specialized columns.Aim. The aim of this study is to develop a method for tranexamic acid in human plasma by high performance liquid chromatography with tandem mass-spectrometry (HPLC-MS/MS) for pharmacokinetic studies.Materials and methods. Determination of tranexamic acid in plasma by HPLC-MS/MS. The samples were processed by acetonitrile protein precipitation.Results and discussion. This method was validated by next parameters: selectivity, matrix effect, calibration curve, accuracy, precision, recovery, lower limit of quantification, carry-over effect and stability.Conclusion. The method of the determination of tranexamic acid in human plasma was developed and validated by HPLC-MS/MS. The linearity in plasma sample was achieved in the concentration range of 100.00–15000.00 ng/ml. Method could be applied to tranexamic acid determination in plasma for pharmacokinetics and bioequivalence studies.